Fear of terrorism: media exposure and subjective fear of attack. Issue 1 (2nd January 2019) - Williamson, Harley; Fay, Suzanna; Miles-Johnson, Toby
ABSTRACT: In many Western countries, citizen knowledge of terrorist events is intrinsically shaped by the style of broadcasted messages published by the media. Media discourses regarding terrorist acts raise questions about how such rhetoric elicits fear in people who typically experience such events through news reports. However, we do not fully understand the impact of the media on perceptions of terrorism as clearly as we understand the relationship between the media and fear of crime. This study examines how media sources accessed actively (e.g. through newspapers; Internet) or passively (e.g. through television; radio) influence knowledge and fear of terrorism. We find receiving information about terrorism from multiple media sources increases fear of terrorism, but media sources accessed passively are not as influential as media sources accessed more actively. These results highlight how media consumption from various sources may affect one's fear of terrorism, and further illustrates how the role of perceived knowledge may exacerbate or mitigate fear. Implications for policy and practice are discussed.